Pemberantasan Kanker di Yogyakarta - Soeripto, Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Cimpaign against cancer is not only the duty of the medical professional but also the responÃ¢â¬Â¢ sibility of the society. The activities of the Sardjito Teaching Hospital Cancer Team. "Kucala" Cancer Society, county hospitals, health centres and physicians in private practice are presented.It is clear that the role of the Cancer Team of the Medical Faculty/the SardjitO Teaching Hospital, "Kucala" Cancer Society and medical professionals are very important in the detection of cancer. Due to the lack of facilitiei and based on the situation of the Yogyakarta area, it seems that there are many problems to deal with.It is suggested that a well organized cancer society will be able to solve the problems.Key Words: cancer - community health - anti-cancer campaign - health organization -- early diagnosis